Even in Sweden : racisms, racialized spaces, and the popular geographical imagination - Pred, Allan, 1936-2007 (University of California Press, 2000)
Allan Pred writes compellingly about the reawakening of racism throughout Europe at the end of the twentieth century--even in Sweden, a country widely regarded as the very model of social justice and equality. Many thousands of non-European and Muslim immigrants and refugees who took advantage of Sweden's generous immigration policies now find themselves the object of discrimination and worse.